VD_FINDINFO Jug / 2014 / 330 vom 7. September 2012 - VD Tribunal cantonal (2012)
DEMANDE ADRESSÉE À L'AUTORITÉ, RÉVISIONDÉCISION, DÉCISION D'IRRECEVABILITÉ | 410 al. 1 let. a CPP (CH), 411 CPP (CH), 412 al. 2 CPP (CH)